Distrust in the Healthcare System and Organ Donation Intentions Among African Americans - Russell, Emily (2012)
The purpose of this study is to further understanding of the association between distrust in the healthcare system and written and verbal expressions of donation intentions among African Americans. We hypothesize that distrust in the healthcare system will be significantly, positively associated with both verbal and written donation intentions. Five hundred and eighty five participants completed a 98-item survey that included scales on distrust in the healthcare system and donation intentions. Bivariate analyses (t-tests, ANOVA, chi-square tests and odds ratios) were used to explore the extent to which donation intentions and distrust in the healthcare system varied by demographic characteristics and the association between the distrust in the healthcare system scale and verbal and written donation intentions. Separate logistic regressions were performed with each of the dependent variables to see if significant associations remained while controlling for confounders. Findings based on the multiple regression indicate that when controlling the participant’s education level, distrust in the healthcare system was not significantly related to written donation intentions (OR = 1.04; P = .12). When controlling for education level, health insurance status, Community Health Advocates group and marital status, distrust in the healthcare system was significantly associated with verbal donation intentions (OR = 1.08; P < 0.05). Our results suggest that distrust in the healthcare system varies in the way that it is associated with donation intentions. Future organ donation studies should be conducted to determine the pathways through which distrust in the healthcare system impacts different types of organ donation intentions.